Sex differences in the agreement between left ventricular ejection fraction measured by myocardial perfusion scintigraphy and by echocardiography. (March 2020) - Jaker, Sams; Burgan, Amjad; Prakash, Vineet; Birkinshaw, Alexander; Moosai, Kishan; Jacques, Adam; Fluck, David; MacGregor, Mark; Lazariashvili, Otar; Sharma, Pankaj; Fry, Christopher H; Han, Thang S
Background: Left ventricular ejection fraction (LVEF) is generally measured by echocardiography but is increasingly available with myocardial perfusion scintigraphy. With myocardial perfusion scintigraphy, the threshold of LVEF below which there is a risk for myocardial infarct or sudden cardiac death is higher for women (51%) than for men (43%). We tested the hypothesis that such a sex difference may also occur with echocardiography and myocardial perfusion scintigraphy. Methods: Four hundred and four men, mean age = 67.7 ± SD = 12.3 yr; 339 women, 67.7 ± 11.7 yr had separate myocardial perfusion scintigraphy and echocardiography examinations within six months. A subset of 327 of these patients (181 men, 68.8 ± 12.1 yr; 146 women, 66.4 ± 12.1 yr) had examinations within one month and were additionally analysed as this sub-group. Myocardial perfusion scintigraphy and echocardiography were used to measure LVEF at rest and their agreement (neither considered as a reference method) was assessed by Bland–Altman plots: LVEF difference (myocardial perfusion scintigraphy minus echocardiography ) against average LVEF (MPS + Echo 2 ). Results: Of patients who had myocardial perfusion scintigraphy and echocardiography performed within six months, mean LVEF difference = +1.1% (95% limits of agreement: −19.3 to +21.6) in men but +10.9% (−10.7 to +32.5) in women. LVEF difference diverged from zero marginally in men (mean difference = +1.1, 95%CI  = +0.1 to +2.1, p  =  0.028) but more in women (+10.9, +9.8 to +12.1, p  < 0.001). The LVEF difference correlated with average LVEF itself in both men ( r  =  0.305, p  < 0.001) and women ( r  =  0.361, p  < 0.001), and with age in women ( r  = 0.117, p  = 0.031). Similar results were observed for the subset. Conclusions: Caution should be taken when interpreting LVEF measured by different techniques due to their wide limits of agreement and systematic bias, more markedly in women.